TINJAUAN ATAS PROSEDUR PENYUSUNAN LAPORAN REALISASI ANGGARAN PADA SEKRETARIAT DPRD PROVINSI DKI JAKARTA - Itsnani Nur Rizky (2020)
This Final Report is carried out in January - March 2020 at the Secretariat of the Regional Representatives Council of DKI Jakarta Province, located at Jl. Kebon Sirih No. 18, Gambir, Central Jakarta, DKI Jakarta Province 10110. The Purpose of this Final Report is to know the Procedure for Preparing Budget Realization Report Starting from document collection, document processing, anda document verification before being input into the Budget Realization Report form.Budget Realization Report is a form of Budget Accountability Repot Provide. The contets of the Budget Realization Report outline are a comparison between the realization and the budget during one reporting period. In addition to know the procedure for Preparing the Budget Realization Report, this final report also purpose is to review The Secretariat DPRD of DKI Jakarta Province has applied accrual based PP No. 71 Tahun 2010 about Government Accounting Standards. Another purpose is to know the strategies so that the absorption of budget funds can be maximized. The Secretariat DPRD of DKI Jakarta Province in the preparations of Financial Statement is guided by The Legislation, Central Government Regulations, Regional Regulation, and Governor Regulation.